Motivasi dan Semangat Belajar Siswa Pada Pembelajaran PAI Studi Kasus di MTs Raudlatul Muta’allimin Babat Lamongan - Khoirul Umam; Imron Arifin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study will discuss the application of the Apperception Patron Client (APC) strategy in increasing student motivation and enthusiasm for learning "a case study at MTs Raudlatul Muta'allimin Babat Lamongan". Using the Apperception Patron Client (APC) strategy is expected to be able to increase student motivation and enthusiasm for learning. Because if students are motivated and have enthusiasm in learning these students can achieve what is their goal. This type of research is qualitative research and is included in qualitative field research using a case study approach. The data generated in this study are primary data and secondary data. Data collection techniques used in this study were observation, interviews and documentation. These data before being made into conclusions the data must go through the stages of data reduction, data presentation and drawing conclusions. In this study, the following results were obtained: The level of motivation and enthusiasm for student learning in PAI lessons at MTs Raudlatul Muta'allimin can be increased by using the Apperception Patron Client (APC) strategy. Which is evidenced by the many students who are motivated and passionate about learning which can be proven by the many students who are motivated to learn, students become studious, not easily discouraged and in other ways. The application of the Apperception Patron Client (APC) strategy is carried out at the beginning of learning. Supporting factors in implementing the Apperception Patron Client (APC) strategy are a conducive classroom atmosphere, adequate infrastructure, good relationships between teachers and students. Meanwhile, the inhibiting factor from the application of the Apperception Patron Client (APC) strategy is the absence of active communication between teachers and students.